Distinção entre areias eolicas e praiais pele analise discriminante - Landim, P. M B; Castro, P. R M (My University, 1981)
Beach deposits occur in high energy environments with continual sorting by swash and backswash. The fines are removed by the backswash, which is not competent to remove the coarser material. Hence negative asymmetry (skewness) results. The wind transports only the finer fraction to the dunes, resulting in a tendency towards a positively skewed distribution. In the case studied the aeolian sand has a mean asymmetry of 0.13, the beach sand -0.11. Equivalent values for mean grain size and standard deviation are 2.51 and 0.24 (aeolian) and 2.41 and 0.37 (beach). Beach sands are therefore coarser and less well sorted than aeolian sands. -V.Gardiner
Distinction between aeolian sand and beach sand by discriminant analysis